Our Digital Footprints during Online Service Learning From Home Program”: EFL Pre-Service Teachers’ Photovoice Analysis - Riski Riski; Suhartini Syukri; Sitti Nurfaidah; Azwar Abidin (International Journal of Transdisciplinary Knowledge, 2021)
The major purpose of this narrative study is to investigate the EFL pre-service teachers’ digital footprints in using digital tools during online service learning from home program in the time of COVID-19. The data in this study is drawn from five EFL pre-service teachers’ photovoices they have narrated on daily reports while conducting the online service learning program amidst the COVID-19 pandemic. The researcher accessed their daily reports page on academic information system (SIA) freely to collect five participants’ narrative photovoices. Then, those photovoices were analyzed using thematic analysis (TA) adopted from Braun and Clarke (2006) through coding the data by underlining code. Their photovoice revealed that all pre-service teachers have been engaged with digital skill, digital literacy, and community development leaving a plethora of digital footprints in the virtual world. However, this study implies that they were more creative in producing beneficial content for the wider community using many applications even though during the COVID-19 lockdown